2012
DOI: 10.3945/ajcn.111.029330
|View full text |Cite
|
Sign up to set email alerts
|

Epicatechin ingested via cocoa products reduces blood pressure in humans: a nonlinear regression model with a Bayesian approach

Abstract: Blood pressure reduction by consumption of cocoa products depends on the dose of ingested epicatechin, which explains most of the between-study differences in classical meta-analyses. Similar effects may be achieved by consumption of other foods that are also rich in epicatechin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 64 publications
3
56
0
1
Order By: Relevance
“…Although cocoa-based supplements and dark chocolate typically contain several different classes of flavanoids, cocoa-induced reductions in blood pressure have been specifically attributed to the quantity of EPI consumption (9,24,40). The reduced MAP reported presently was likely the result of slight improvements in peripheral vascular function given that similar HRs and skeletal muscle blood flows between control and EPI groups suggest unchanged cardiac outputs.…”
Section: Epi Administration Cardiovascular Hemodynamics and Muscle mentioning
confidence: 79%
“…Although cocoa-based supplements and dark chocolate typically contain several different classes of flavanoids, cocoa-induced reductions in blood pressure have been specifically attributed to the quantity of EPI consumption (9,24,40). The reduced MAP reported presently was likely the result of slight improvements in peripheral vascular function given that similar HRs and skeletal muscle blood flows between control and EPI groups suggest unchanged cardiac outputs.…”
Section: Epi Administration Cardiovascular Hemodynamics and Muscle mentioning
confidence: 79%
“…Many studies have focused on the protective effects of pure (-)-epicatechin in the cardiovascular system . For example, it has been shown that (-)-epicatechin improves vascular function in humans, as evaluated by measuring flow mediated dilation, and that its content correlates with blood pressure lowering effect of flavanol-rich food (Ellinger et al, 2012;Schroeter et al, 2006). In addition, experiments in animal models have also demonstrated that (-)-epicatechin prevents and reverses hypertension, improves endothelial dysfunction, reduces the vascular oxidative stress and proinflammatory status, early events involved in development of atherosclerosis and insulin resistance (Galleano et al, 2013;Gó-mez-Guzmán et al, 2012Litterio et al, 2012;VazquezPrieto et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…cocoa and dark chocolate) has been associated with a reduced risk for cardiovascular diseases (CVD) (15). Evidence suggests that the beneficial effects of cacao-based products may be mediated by improving endothelial function primarily, through an increase in the production of nitric oxide (NO) (3).…”
Section: Introductionmentioning
confidence: 99%